Growth and Welfare Implications of Mortality Differentials in Unfunded Social Security Systems. (March 2022) - Kelly, Mark C.
Several recent studies have examined the steady-state welfare implications of mortality differentials within unfunded Social Security systems, concluding that these differentials undermine the progressivity of the system and make society worse-off relative to alternative public pension schemes. This study is the first to systematically investigate the long-run implications of mortality inequality within the U.S. Social Security system. Utilizing an OLG endogenous growth model of the U.S. economy, I compare the current pay-as-you-go (PAYG) system to versions of the model without either mortality differentials or income inequality. I find that the assumption of mortality homogeneity biases the equilibrium growth rate and welfare analysis. The PAYG system is also compared to a fully funded system based on capital subsidies. The model predicts that PAYG suppresses growth and that, for a given range of subsidy rates, the fully funded system Pareto dominates PAYG in both the medium-run and the long-run.